The Russia-Ukraine crisis presents threats to Nigeria’s food security, but potential opportunities for the fertilizer, energy sectors - Balana, Bedru; Andam, Kwaw S.; Amare, Mulubrhan; Adeyanju, Dolapo; Laborde Debucquet, David (International Food Policy Research Institute, 2022)
The current rise in global market prices for major food commodities almost mirrors that of the 2008 food crisis, presenting a worldwide threat to food security. The situation is particularly severe in Africa, where the COVID-19 pandemic and now the Russia-Ukraine crisis have exposed the vulnerability of food systems to major shocks, particularly in countries like Nigeria that rely heavily on imports of major staple foods such as rice and wheat.